Characterisation of the innate immune response to Campylobacter jejuni colonisation in the chicken intestine - Shaughnessy, Ronan (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2011)
Campylobacter jejuni is the leading cause of gastroenteritis in humans, and chickens are the primary vector for infection. The microbe colonises the caeca of birds as a commensal, and it is hypothesised that intestinal defences regulate colonisation. Identifying birds with enhanced abilities to clear C. jejuni would enable the selective breeding of colonisation resistant birds. However, the caecal immune response to C. jejuni has been poorly characterised to date and is the basis of this thesis.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin.